Patient‐controlled analgesia at the end of life at a pediatric oncology institution. Issue 7 (27th March 2015) - Anghelescu, Doralina L.; Snaman, Jennifer M.; Trujillo, Luis; Sykes, April D.; Yuan, Y.; Baker, Justin N.
Abstract Background Patient controlled anesthesia (PCA) is increasingly used to manage pain in pediatric cancer patients and is important in the treatment of escalating pain at the end of life. The description of the use of opioid PCA in this population has been limited. Procedure This retrospective chart review of the last 2 weeks of life addressed the following objectives: (1) to describe the patient population treated with opioid PCA; (2) to describe the morphine‐equivalent doses (MED) (mg/kg/day); and (3) to describe the pain scores (PS). Results Twenty‐eight percent of inpatients used opioid PCA for pain control during the last 2 weeks of life. The mean MED (mg/kg/day) (SD) at 2 weeks prior and the day of death were 10.7 (17.9) and 19 (25.8). The mean MED increased over the last 2 weeks of life for all patients and across age groups and cancer diagnoses (all P < 0.05). The mean MED was significantly higher in the younger age group (age <13 vs. age ≥13) on the day of death (P < 0.04). There was a significant change in mean PS over the last 2 weeks of life (P < 0.001), with the highest PS on the day before death. The most frequently used concurrent medications were benzodiazepines (91%). Conclusions Children and young adults with cancer experience high opioid requirements and significant dose increases during the last 2 weeks of life. Additionally, PS increase toward the end of life. Opioid rotation and addition of adjuvant medications merit consideration in the context of escalating opioid requirements. Pediatr Blood Cancer 2015;62:1237–1244. © 2015 Wiley Periodicals, Inc.